UPAYA MENINGKATKAN HAFALAN QS.AL-FATIHAH SISWA/I MELALUI STRATEGI PEMBELAJARAN AUDIO VISUAL PADA KELAS I SD NEGERI 106162 MEDAN ESTATE - Lilik Sumarni (Universitas Negeri Medan, 2019)
This study aims: To determine the application of the Audio Visual Learning learning strategy in memorizing QS. Al Fatihah; To find out the increase in memorization of odd semester I students of SDN 106162 Medan Estate in the application of Audio Visual Learning strategies in memorizing QS. Al Fatihah. This study used an interactive qualitative method and the PTK class action research approach was carried out with 2 cycles. Each cycle includes planning, implementation, observation and reflection. The subjects of this class action research are first grade students of SDNegeri 106162 Medan Estate. From the research conducted by examining the students' initial conditions as measured by the QS memorization test kits. Al-Fatihah with 2 cycles, it was seen that there was an increase in memorization results achieved by students in memorizing QS. Al Fatihah. Based on data analysis, it can be concluded that in cycle 1 the completeness of memorizing students is only 35.37%, while in cycle 2, the QS strategy is applied. Al-Fatihah increased to 85.76%. Student responses also increased, data from observations on student activities from 35.37% in cycle 1, increased in cycle 2 to 85.00%. Keywords: Memorization, Media, Audio Visual